Studi Studi Profil Awan Konvektif Penyebab Hujan Es Di Jakarta Dengan Menggunakan Radar Cuaca (Studi Kasus Hujan Es Di Jakarta 17 Desember 2022) - haryadi, Haryadi; Mahendra Putra, Richard; Widodo, Pujo (UNIB Press, 2024)
On December 17th 2022 there was hail in the Jakarta area. This phenomenon is unique and rarely occurs in the Equator region. This research was carried out by analyzing the profile of the convective clouds that produce hail using weather radar data. Data analysis was carried out by looking at factors from global, regional and local atmospheric conditions that caused the convective system to occur in Jakarta on that date. Then analyze the convective cloud structure that causes hail and estimate the probability of hail events based on ZHAIL products from weather radar. The hail that occurred in Jakarta was caused by convective clouds which occurred due to fairly unstable atmospheric conditions and was supported by weather factors on a global and regional scale. This results in the formation of cumulonimbus clouds with a strong updraft mechanism, characterized by the presence of a weak echo region (WER) and overhang echo (OE) during the cloud growth phase. Then, in the mature phase, the ice particles contained in the cumulonimbus cloud are quite large as indicated by the three body scatter spike (TBSS) pattern. The ZHAIL product shows that there is a chance of hail that is detected since the growth phase of the convective cloud and this condition consistently persists until just before the convective cloud produces hail. When hail occurs, the probability value of the hail event based on the ZHAIL product in this case study actually decreases and disappears in the radar image at a later time.